The bone spindle - Vedder, Leslie (Razorbill, 2022)
Fi, a bookish treasure hunter who doesn't believe in true love, is pricked in the finger by a bone spindle while exploring an ancient ruin and cursed to be paired with the spirit of the Prince Briar Rose, whose body has been asleep for 100 years waiting for a magic, true love kiss. Shane, a lesbian warrior girl, may be able to help Fi and Briar Rose break the curse, but an evil Witch might steal Shane's heart before she can, threatening everything Fi and Briar hope for.